Argatroban is stable in citrated whole blood for 24 hours. (29th April 2018) - Guy, S.; Kitchen, S.; Van Veen, J. J.
Abstract: Introduction: Argatroban is a direct thrombin inhibitor used as an anticoagulant for patients who have Heparin induced thrombocytopenia. Quantification can be performed using a dilute thrombin time or anti‐iia assay. Our preferred method is Hemoclot Thrombin Inhibitor Assay (HTI).To the best of our knowledge, no one has published on the stability of plasma argatroban in whole citrated blood at room temperature. Methods: Forty matched samples obtained from 4 patients receiving argatroban. 1 mL of the whole blood was removed from the sample into a labelled plastic tube and left on the laboratory bench at room temperature for 24 hours prior to centrifugation. The remaining sample was spun at 2000  g for 10 minutes and the plasma aliquoted off and labelled 0 hour and stored at −80°C prior to testing. At 24 hours the plastic tube containing whole blood was centrifuged at 2000  g for 10 minutes and the plasma aliquoted off and labelled 24 hours and stored at −80°C prior to testing. HTI assay was used for plasma argatroban determination. Results: The lowest argatroban level obtained was 0.16 μg/mL at 0 hour; 0.18 μg/mL at 24 hours from the same pair, the highest argatroban level obtained was 1.72 μg/mL at 0 hour;1.76 μg/mL for the same pair at 24 hours. The mean result for 0 hour was 0.57 μg/mL and 0.60 μg/mL at 24 hours. Conclusion: This study proposes that patients receiving treatment in hospitals who cannot provide a dedicated argatroban plasma concentration method could have their samples sent on whole blood within 24 hours of venepuncture to a laboratory who could provide the test.